SAT0089 The impact of periodontal disease on early inflammatory arthritis persists even after all teeth are lost. (23rd January 2014) - Westhoff, G.; Dietrich, T.; Schett, G.; de Pablo, P.; Zink, A.
Abstract : Background: Data suggests that individuals with periodontal disease (PD) may be more likely to develop rheumatoid arthritis (RA) and have worse disease activity. PD is a common inflammatory disease characterized by gingival accumulation of inflammatory cells with endothelial cell proliferation and matrix degradation that may worsen joint inflammation. Since PD is a major cause of tooth loss, tooth loss may be a surrogate marker for chronic PD, an inflammatory process that may possibly end when the last tooth is lost. We therefore hypothesized that partial vs. complete tooth loss (edentulism) may be differentially associated with disease activity in persons with early arthritis naive to DMARD-therapy. Objectives: To determine whether tooth loss and arthritis activity are interrelated by comparing DMARD-naive patients with complete tooth loss to those with partial or no tooth loss with regards to disease activity at arthritis onset. Methods: The study included 1, 009 patients with early arthritis (<6 months) naive to DMARD-treatment, enrolled in a longitudinal study (CAPEA 2010-2013). Data collection included disease activity (DAS28 calculated by TJC28, SJC28, ESR and Patient Global (PG; NRS 0-10)), the 2010 ACR-EULAR RA classification criteria and self-reported number of teeth. Patients were categorized according to number of teeth at study entry (no teeth, 1-19, 21-27, all teeth). Analysis of covariance was done to determine baseline disease activity by number of teeth. Results: Study participants (65% female) were 55±14 years old and had mean symptom duration of 12±7 weeks. 56% were RF or ACPA pos. and 66% fulfilled the 2010 criteria for RA. No patient had received any DMARDs at baseline. Sample characteristics by tooth loss categories are shown on Table . Significantly more patients with edentulism met ACR/EULAR classification compared with those with complete dentition (OR 1.9, 95% CI 1.01-3.35; adj. for age, sex, BMI, smoking, and DAS28). Edentulous patients had neither lower nor higher disease activity (DAS28) than patients with considerable tooth loss (1-19 teeth). However, compared with those with moderate tooth loss (20-27; P=0.046) or complete dentition (P=0.006), they had significantly worse disease activity. Conclusions: Tooth loss was associated with disease activity at disease onset in a large cohort of patients with early inflammatory arthritis (IA) naïve to DMARD-therapy. Contrary to the assumption that exposure to PD ends once all affected teeth are lost, edentulism does not improve the interrelation of dental health and IA. The impact of PD on IA starts before IA onset, and obviously persists even after all teeth have been lost. The data also support the notion that there might be a common underlying pathobiology for both conditions. Disclosure of Interest: None Declared